The Extent to Which the Internal audit function contributes to improving administrative performance: A field study in the Baghdad Health Department / Rusafa (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract:                The internal audit is considered the safety valve for senior management in all institutions. It aims to protect property, and raise the efficiency and effectiveness of the administrative performance, by following up on compliance with laws and instructions and the application of regulations in a way that increases the administrative performance of the department. The internal audit is possible to determine Weaknesses or imbalances in the administrative performance. To achieve this goal, an analytical descriptive methodology was adopted. The Baghdad Health Department / Al-Rosana was considered as society for this study. Thus, a questionnaire of 44 items was designed in order to cover all related topics. The questionnaire was distributed and 126 answers were collected. The statistical program (SPSS)) was used to examine selected answers. The study reported the efficiency of the internal audit in the Baghdad Health Department / Al-Rosana.  This does not prevent the existence of some weaknesses, as the internal audit helps by detecting deviations and errors in all aspects of administrative performance, in raising the level of the department. Reaching several conclusions, the most important is that internal audit helps improve administrative performance in various aspects of the organization's activities, through which internal audit helps to detect deviations and errors in all respects administrative performance.